Perubahan Fonologis Bahasa Gaul dalam Percakapan Whatsapp Kelompok Siswa Kelas 9 MTs Muhammadiyah 05 Kemusu - Wahyu Oktavia (ESTETIK : Jurnal Bahasa Indonesia, 2020)
The study entitled "Phonological Changes in Slang in Conversations Whatsapp Groups of 9th Grade Students Muhammadiyah 05 Kemusuâ€ aims to analyze the field of phonological studies in slang. This study uses a descriptive qualitative method that produces descriptive data in the form of written or oral words from people and observable behavior. The data source of this research is the form of Whatsapp group chat. The object in this study is slang. The subjects chosen are 9th grade students of MTs Muhammadiyah 05 Kemusu. The data analysis technique uses data reduction, data presentation, and verification. The results of the study show that (a) there is a form of slang; (b) there are 50 forms of slang which are transcribed in phonetic and phonemic forms; (c) there areÂ  9Â  phonological traits in slang which are classified based on changes in consonant phoneme, vocal, mixed, combination of phonemes, anaphylaxis or phoneme addition, contraction or shortening, acronym, metathesis, and diphthongized or semivowel; and (d) the causes of the use of slang language are friendship, prestige, age, gender, and technological development